2011
DOI: 10.1007/s11010-011-0876-4
|View full text |Cite
|
Sign up to set email alerts
|

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro

Abstract: PTP1B is a negative regulator of insulin signaling pathway. This study investigated the effects of compound CCF06240, a PTP1B inhibitor, on insulin sensitivity and lipid metabolic abnormalities in vivo and in vitro, respectively. The insulin resistant IRM mouse model was induced by HFD. The responses to insulin were determined by OGTT, ITT, and hyperinsulinemic-euglycemic clamp test. The body weight and the levels of serum TC and TG were measured to estimate the lipid metabolism in vivo. Recombinant human GST-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…Interestingly, data from Elchebly et al (1999) and our laboratory (Panzhinskiy et al, 2013) showed that PTP1B knockout reduced body weight in mice receiving high-fat content diet, but not control chow, which is consistent with the effect of CNB-001 treatment on body weight only in high-fat diet-fed mice. Our docking simulation studies confirmed that CNB-001 can bind and potentially inhibit PTP1B, and thus the effects of CNB-001 administration on insulin resistance, adiposity, weight gain, and glucose metabolism in obese mice can be attributed to PTP1B inhibition, as seen in the case of other reported inhibitors of PTP1B (Lantz et al, 2010;Ma et al, 2011). For example, a recent study showed that novel proteoglycan PTP1B inhibitor FYGL decreased the plasma glucose level by the mechanism of inhibiting PTP1B expression and activity, consequently regulating the tyrosine phosphorylation level of the IR-b subunit and the level of hepatic glycogen, thus resulting in improved of insulin sensitivity in db/db mice (Wang et al, 2012).…”
Section: Cnb-001 Alleviates Insulin Resistancesupporting
confidence: 70%
“…Interestingly, data from Elchebly et al (1999) and our laboratory (Panzhinskiy et al, 2013) showed that PTP1B knockout reduced body weight in mice receiving high-fat content diet, but not control chow, which is consistent with the effect of CNB-001 treatment on body weight only in high-fat diet-fed mice. Our docking simulation studies confirmed that CNB-001 can bind and potentially inhibit PTP1B, and thus the effects of CNB-001 administration on insulin resistance, adiposity, weight gain, and glucose metabolism in obese mice can be attributed to PTP1B inhibition, as seen in the case of other reported inhibitors of PTP1B (Lantz et al, 2010;Ma et al, 2011). For example, a recent study showed that novel proteoglycan PTP1B inhibitor FYGL decreased the plasma glucose level by the mechanism of inhibiting PTP1B expression and activity, consequently regulating the tyrosine phosphorylation level of the IR-b subunit and the level of hepatic glycogen, thus resulting in improved of insulin sensitivity in db/db mice (Wang et al, 2012).…”
Section: Cnb-001 Alleviates Insulin Resistancesupporting
confidence: 70%
“…Inhibition improves insulin sensitivity and reduces body weight, total cholesterol and triglycerides in high fat diet fed mice 189 …”
Section: Figurementioning
confidence: 99%
“…Because PTPs are implicated in the pathophysiology of various disorders, many of them have been identified as potential new targets for novel drug discovery. A number of PTP inhibitors have been developed (6,9,45,68,81,93). Some of them have been proven to be efficient in lowering blood glucose levels in vivo or in inhibiting tumor xenograft growth (93).…”
Section: Introductionmentioning
confidence: 99%